LINC00662 modulates cervical cancer cell proliferation, invasion, and apoptosis via sponging miR‐103a‐3p and upregulating PDK4. Issue 6 (5th April 2021) - Liu, Yongli; Qiu, Shuang; Zheng, Xiaoli; Qiu, Yingying; Yao, Shenghui; Ge, Yan; Zhou, Caixia
Abstract: Cervical cancer (CC) is one of the most common cancers among women with high recurrence rates all over the world. Recently, the molecular mechanism of CC has been gradually uncovered in accumulating reports. This study aimed to investigate the function and upstream regulation mechanism of pyruvate dehydrogenase kinase 4 (PDK4) in CC cells, which was verified as an oncogene in several cancers. Through RT‐qPCR assay, we discovered that PDK4 was highly expressed in CC cells. Then, it was demonstrated in function assays that PDK4 facilitated CC cell proliferation and invasion, but inhibited CC cell apoptosis. Next, we sought to determine the upstream genes of PDK4, and miR‐103a‐3p was identified to target PDK4. Then, through bioinformatics tools and a range of mechanism assays, long intergenic non‐protein coding RNA 662 (LINC00662) was verified as the sponge of miR‐103a‐3p. Moreover, LINC00662 positively modulated PDK4 expression via competitively binding to miR‐103a‐3p in CC cells. Subsequently, rescue assays demonstrated that LINC00662 accelerated CC cell proliferation and inhibited cell apoptosis through upregulating PDK4. Furthermore, forkhead box A1 (FOXA1) was verified to activate transcription of both LINC00662 and PDK4. Taken together, our study revealed a novel ceRNA pattern of LINC00662/miR‐103a‐3p/PDK4 with FOXA1 as a transcription factor of LINC00662 and PDK4 in CC cells.